Keragaman dan Resistensi Antibiotik Isolat Bakteri Tanah di Dalam dan Luar TPU Bonoloyo, Surakarta Jawa Tengah - Yusnita Rahmawati; Triastuti Rahayu; Erma Musbita Tyastuti; Yasir Sidiq (Pharmacon: Jurnal Farmasi Indonesia, 2023)
A cemetery acts as an active decomposition site and contains bacteria which most likely have antibiotic resistance. However, related data to the phenomenon is limited. This study aimed to compare the diversity of bacteria inside and outside the cemetery and examine bacterial antibiotic resistance. First, samples were collected from three different spots inside and outside the Bonoloyo public cemetery in Surakarta, Central Java. Then, the bacteria were isolated by spread plate method on NA medium and were observed using Gram staining after 48 hours of incubation. Also, bacterial resistance against cefepime, bacitracine, and ampicilin were examined. As the results, bacterial populations inside and outside the cemetery area are 3.4x106 and 4.6x106 CFU/gram, respectively, with a diversity of 38% and 34%, while 28% of isolates are collected from both areas. The result of morphological observation showed that 15 and 21 isolates are respectively round and irregular, white to yellow colour with raised (16 isolates) and flat (19 isolates) elevation. Gram staining showed 48 isolates are coccus and 2 are bacilli, with 23 isolates of Gram negative and 27 isolates of Gram positive. Bacterial isolates showed resistance against cefepime (50%-50%)  and against bacitracine (52%-43%) each from both areas of the cemetery, while resistance against ampicilin was relatively low (33%-21%). The number of bacterial populations and bacterial diversity inside and outside the cemetery area are not significantly different. In fact, the resistance of the soil bacteria population collected from cemetery soil are higher than that collected from soil outside the cemetery.